Patent Overview of Innovative Hyaluronic Acid-Based Hydrogel Biosensors - Ahmed Fatimi; Fouad Damiri; Mohammed Berrada; Adina Magdalena Musuc (Biosensors)
Hyaluronic acid-based hydrogels are emerging as highly versatile materials for cost-effective biosensors, capable of sensitive chemical and biological detection. These hydrogels, functionalized with specific groups, exhibit sensitivity modulated by factors such as temperature, pH, and analyte concentration, allowing for a broad spectrum of applications. This study presents a patent-centered overview of recent advancements in hyaluronic acid hydrogel biosensors from 2003 to 2023. A total of 50 patent documents—including 41 patent applications and 9 granted patents—reveal a growing interest, primarily driven by United States-based institutions, which account for approximately 54% of all filings. This trend reflects the strong collaboration between universities, industry, and foundations in pushing this technology forward. Most patented technologies focus on biosensors for in vivo blood analysis, measuring critical parameters such as gas concentration and pH, with particular emphasis on glucose monitoring via tissue impedance using enzyme-immobilized oxidase electrodes. Additionally, the 9 granted patents collectively showcase key innovations, highlighting applications from continuous glucose monitors to implantable vascular devices and sweat analyte detection systems. These patents underscore the adaptability and biocompatibility of hyaluronic acid hydrogels, reinforcing their role in enhancing biosensor performance for real-time health monitoring. In summary, this overview highlights the importance of patent analysis in tracking and directing research and development, helping to clarify the field’s evolution and identify innovation gaps for hyaluronic acid-based hydrogel biosensors.